Alfabetización digital y ciudadanía resiliente: evidencia empírica de futuros docentes chilenos frente a la posverdad - Pereira Barahona, Manuel (2025)
In a context of post-truth and low institutional trust, teacher training acquires strategic relevance. This study investigates the extent to which digital literacy among future teachers strengthens their capacity to detect and counteract fake news in the classroom. A 30-item questionnaire was administered to a convenience sample of 215 future teachers from a Chilean university. A structural equation model was used to examine the relationships between digital literacy, perceived civic responsibility, and pedagogical self-efficacy in the face of disinformation. The model showed a good fit and demonstrated that digital competencies significantly predict civic responsibility and pedagogical self-efficacy. Furthermore, civic responsibility partially mediated the relationship between digital literacy and self-efficacy. These findings support the integration of cognitive media literacy with the concept of resilient citizenship, as they provide evidence of the counter-majoritarian nature of education in polarized contexts.